Development of E-Books as Educational Media to Introduce Disasters to Early Childhood - Heni Nafiqoh; Ratna Dwi Nurcahyani (STAI Hubbulwathan Duri, 2025)
Indonesia's geographical position along the Pacific Ring of Fire makes it highly vulnerable to natural disasters such as earthquakes, floods, and tsunamis. Early childhood education plays a critical role in preparing young learners to recognize hazards and respond appropriately during emergencies. However, disaster education for children is often limited to conventional methods that lack interactivity and developmental alignment. This study aimed to develop and evaluate an interactive e-book designed to enhance disaster preparedness among children aged 4–6 through a developmentally appropriate, engaging, and multimedia-based approach. Using an Educational Design Research (EDR) framework, the study involved iterative phases of needs analysis, product design, expert validation, revision, and limited field testing. Data were collected through interviews, observation sheets, teacher questionnaires, and expert validation rubrics. The e-book incorporated child-friendly illustrations, animations, narration, and interactive games. Expert validators rated the e-book as